dr., SpM: Poster Presentation - Case Report - Ophthalmologist - SAWITRI BOENGAS; Jefman Efendi Marzuki Hy; Debora Ratri Aldora (Majalah Oftalmologi Indonesia, 2023)
Introduction : Cyclopentolate eye drops 1% are frequently used during the cycloplegic refraction test. Cyclopentolate 1% side effects that are neurotoxic have the potential to be fatal but are extremely rare. Case Illustration : Thirty minutes after first drop of the cycloplegic refraction preparation, a 4-year-old kid had neurotoxic effects in the form of anxiety, disrupted communicative interactions, and hallucinations after receiving 3 drops of 1% cyclopentolate. Drug administration was stopped, and the patient was observed in the ER. After stopping the eye drops and being monitored in the ED for two hours, the condition improved. Discussion : Conclusion : Discussion: A cycloplegic medication that affects muscarinic receptors is cyclopentolate 1%. Administering eye drops is supposed to have a local effect on the eyes only, but frequently systemic effects can happen if there is absorption via the mucosa of the throat, nose, and stomach due to the eye drops' flow through the nasolacrimal duct when the medicine is instilled. One of Cyclopentolate's 1% uncommon adverse effects is neurotoxic impact, which can be fatal. When cyclopentolate interacts with the central nervous system's muscarinic receptors, this syndrome may result. The severity of the side effects increases with dosage and administration frequency, age and BMI, and dose. Focusing on the Lacrimal Canal during delivery and using the lowest dose of cyclopentolate are recommended to minimize side effects. Conclusion: Cyclopentolate 1% has a rare but potentially catastrophic side effect called neurotoxicity. Reduce the dosage of cyclopentolate, administer it properly dan using it combination with other cycloplegic can reduce adverse effects.